Penggunaan Teknologi Informasi Komunikasi oleh Pemerintah Kabupaten Kuningan dalam Meningkatkan Pendapatan Asli Daerah - Mubaraq, Banu Sulaeman; Alfita, Aida; Rahma, Anasya Maulikha; Nurfaizi, Dandi Aulia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The use of Information and Communication Technology (ICT) has become one of the strategic efforts of local governments in encouraging the development of the tourism sector. An ICT-based approach, known as e-tourism, enables the marketing of tourist destinations globally without the limitations of distance and time. The implementation of an integrated information system through the Destination Management Organization (DMO) involves collaboration between the government, private sector, and the community, which aims to create sustainable and effective tourism management. However, obstacles such as suboptimal ICT infrastructure, limited resources, and less than optimal coordination between institutions are challenges in implementing this policy. By integrating the principles of good governance, technological literacy, and community participation, Kuningan Regency can strengthen the competitiveness of regional tourism, support local economic growth, and encourage balanced development. This study uses a qualitative descriptive approach to analyze the role of ICT in tourism development in Kuningan Regency and its impact on PAD. The results of the study indicate that optimizing ICT in the tourism sector has great potential to increase the attractiveness of regional tourism while strengthening the position of Kuningan Regency as a superior conservation district in West Java.